Clinical features of conversion disorder. Issue 4 (April 1988) - Grattan-Smith, P; Fairley, M; Procopis, P
Abstract : This study reviewed the case notes of 52 children diagnosed as suffering from hysterical conversion during admission to a paediatric teaching hospital over a 10 year period. The disorder was rare below 8 years of age and girls outnumbered boys three to one. Altogether 75% of the children presented during spring and summer; at the time of end of year exams and the beginning of the new school year. The presentation was usually polysymptomatic with gait disturbance being the main complaint in 36 children. Sensory abnormality, predominantly pain, was present in 40 children; this indicates a strong association between psychogenic pain and conversion disorder in children. At discharge 32 were completely recovered or had appreciably improved. There was a core group that presented particular difficulties with diagnosis and showed little positive response to treatment.